A running breeding program for indigenous chickens in Ethiopia: Evaluation of success - Wondmeneh, E.; Waaij, E.H. van der; Dessie, Tadelle; Okeyo Mwai, Ally; Arendonk, Johan A.M. van (American Society of Animal Science, 2014)
In 2008 a breeding program to increase production level in indigenous chickens was initiated at the Debre Zeit Agricultural Research Center in Ethiopia and is currently producing its 8th generation. Aim of this paper was to evaluate the success of the breeding program. Selection was on own performance for bodyweight at 16 weeks of age (BW16) and for the hens also on cumulative egg number at week 45 of laying (EN45). Heritability for BW16 in the 6th generation (G6) was 0.37, and for EN24 was 0.32. Phenotypic correlation between BW16 and EN24 was 0.36, but genetic correlation was -0.12. Genetic correlations of BW16 with cumulative egg production earlier in the laying series were 0.51 at 8 weeks of laying, decreasing to 0.22 at 16 weeks of laying. The genetic trends were positive for both traits under selection from generation 4 (G4) and G6.